Development and initial validation of a new outcome measure for hospice and palliative care: the St Christopher's Index of Patient Priorities (SKIPP). Issue 2 (16th September 2013) - Addington-Hall, Julia; Hunt, Katherine; Rowsell, Ali; Heal, Rosanna; Hansford, Penny; Monroe, Barbara; Sykes, Nigel
Abstract : Objective: To develop and conduct a preliminary psychometric analysis of a hospice and palliative care patient-reported outcome measure to detect patients' perceptions of change in quality of life (QoL) and issues of concern, and views of service benefit. Methods: Following pilot testing and cognitive interviewing, St Christopher's Index of Patient Priorities (SKIPP) was administered twice to hospice inpatients and homecare patients. QoL was rated 'now', and retrospectively 'before starting hospice care' or 'at the time of the first interview'. Patients nominated and rated progress with main concerns, rated the difference the service was making, and completed palliative care outcome scale. Patients completed SKIPP again within 24 h to measure test-retest reliability. Results: QoL scores 'now' differed significantly from retrospective scores made at same time: QoL increased with hospice care when patients 'looked back' on previous QoL. Four-fifths reported that their first concern had got 'a little'/ 'much' better since initial service contact: this declined subsequently. Four-fifths at both time points said the hospice had made 'a lot of difference' to them. No significant differences were noted between time points on palliative care outcome scale items. Test-retest analyses were prevented by low numbers. Conclusions: SKIPP can detect patients' perception of change in QoL and main concerns, and the difference patients think the service has made to them. Its design with current and retrospective components addresses response shift and means it can be used for quality improvement or clinical purposes with only one administration, an advantage in frail populations. It is therefore a useful addition to hospice and palliative care patient-reported outcome measures.